2011
DOI: 10.1037/a0023908
|View full text |Cite
|
Sign up to set email alerts
|

Personality constellations in incarcerated psychopathic men.

Abstract: Advances in the operationalization of psychopathy have led to an increased understanding of the boundaries, structure, and nomological network of this construct, although significant questions remain. The empirical identification of replicable and theoretically meaningful psychopathy subtypes may help to improve the classification and diagnosis of this condition. We conducted a classification study of 91 incarcerated men who met conventional criteria for high levels of psychopathy using the Psychopathy Checkli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 108 publications
0
17
0
2
Order By: Relevance
“…These protean polarities have reappeared in changing names and guises over the past century, but they display surprising conceptual convergence: the impulsive psychopath versus the swindler psychopath (Kraepelin, ), antisocial personality disorder versus psychopathy (Lilienfeld, ), sociopathy versus psychopathy (Lykken, ; Partridge, ), secondary psychopathy versus primary psychopathy (Karpman, ; Skeem, Poythress, Edens, Lilienfeld & Cale, ), simple versus complex psychopathy (Arieti, ), unsuccessful psychopathy versus successful psychopathy (Hall & Benning, ), nonadaptive versus adaptive sociopathy (Sutker & Allain, ), and aggressive versus emotionally stable psychopathy (Hicks, Markon, Patrick, Krueger, & Newman, ). Corroborating these overlapping distinctions, cluster analyses support the existence of separable secondary and primary “subtypes” among high scorers on the PCL‐R (e.g., Blagov et al., ) and PPI (e.g., Falkenbach, Stern, & Creevy, ), although these subtypes are almost certainly densifications of multiple dimensions in multivariate space rather than genuine taxa (Edens et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…These protean polarities have reappeared in changing names and guises over the past century, but they display surprising conceptual convergence: the impulsive psychopath versus the swindler psychopath (Kraepelin, ), antisocial personality disorder versus psychopathy (Lilienfeld, ), sociopathy versus psychopathy (Lykken, ; Partridge, ), secondary psychopathy versus primary psychopathy (Karpman, ; Skeem, Poythress, Edens, Lilienfeld & Cale, ), simple versus complex psychopathy (Arieti, ), unsuccessful psychopathy versus successful psychopathy (Hall & Benning, ), nonadaptive versus adaptive sociopathy (Sutker & Allain, ), and aggressive versus emotionally stable psychopathy (Hicks, Markon, Patrick, Krueger, & Newman, ). Corroborating these overlapping distinctions, cluster analyses support the existence of separable secondary and primary “subtypes” among high scorers on the PCL‐R (e.g., Blagov et al., ) and PPI (e.g., Falkenbach, Stern, & Creevy, ), although these subtypes are almost certainly densifications of multiple dimensions in multivariate space rather than genuine taxa (Edens et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…Secondary psychopaths are believed to develop their callous interpersonal styles as a result of exposure to harsh, stressful life circumstances relative to "primary [psychopathy], in which neither neurotic motivations, hereditary taint, nor dissocial nurture seem to be determining factors" (Lykken, 1957, p.6). The existence of a theoretically consistent high-anxious secondary psychopathy variant, which is supported by empirical work (Blagov et al, 2011;Poythress et al, 2010), may explain inconsistent correlations reported among measures of psychopathy and anxiety.…”
Section: Cu Traits and Negative Life Events 17mentioning
confidence: 87%
“…In contrast, incarcerated adults with high levels of both psychopathy and anxiety exhibit higher rates of abuse and trauma (Blagov et al, 2011; Poythress et al, 2010), higher levels of impulsivity (Poythress et al, 2010), anger (Blagov et al, 2011), as well as reactive (Falkenbach, Poythress, & Creevy, 2008) or dating (Vidal, Skeem, & Camp, 2010) aggression than their nonanxious counterparts. These findings are consistent with the contention that this latter group shows problems in regulating emotion and behaviour related to past traumatic experiences (Skeem et al, 2003).…”
mentioning
confidence: 99%
“…Further, prior research examining differences between primary and secondary psychopathy groups on the CU dimension of psychopathy have typically found these two groups do not differ on their level of CU traits in either adult (Blagov et al, 2011; Hicks, Markon, Patrick, Krueger, & Newman, 2004; Poythress et al, 2010; but see Vassileva, Kosson, Abramowitz, & Conrod, 2005) or adolescent (Kimonis et al, 2012) samples. Given that these two groups both show high rates of CU traits, different etiological underpinnings to primary and secondary psychopathy should also be critical for understanding children high on CU traits.…”
mentioning
confidence: 99%